Literature Review: Kualitas Hidup Pasien Carpal Tunnel Syndrome - Ica Pratiwi; Pagan Pambudi; Pandji Winata Nurikhwan; Muhammad Welly Dafif; Mohammad Bakhriansyah (Homeostasis, 2022)
Abstract: Carpal tunnel syndrome (CTS) is the most common type of peripheral mononeuropathy. CTS can interfere with a person's quality of life both physically and mentally and result in patients experiencing disturbances in their quality of life. The purpose of writing this literature review is to determine the quality of life of patients with Carpal Tunnel Syndrome. The reference data in this article review was obtained by searching using PubMed, Science Direct, and Google Scholar published from 2011 to 2021. After the search and article selection process, 10 articles were found that were included in this literature review. Of all the articles, there is one article which shows that Carpal Tunnel Syndrome does not affect the quality of life. While nine other articles show that Carpal Tunnel Syndrome can affect quality of life. Hand pain and dysfunction result in limited activity so this is related to bodily, psychological and social functions. The symptoms experienced by CTS patients cause increased anxiety, depression, limited daily activities, decreased effectiveness at work, and decreased sleep quality, causing patients to experience disturbances in their quality of life. Keywords : Carpal Tunnel Syndrome, quality of life, physical and mental health Abstrak: Carpal Tunnel Syndrome (CTS) merupakan jenis mononeuropati pererifer yang paling umum ditemui. CTS dapat mengganggu kualitas hidup seseorang baik secara fisik maupun mental dan mengakibatkan pasien mengalami gangguan dalam kualitas hidup mereka. Tujuan penulisan literature review ini adalah untuk mengetahui kualitas hidup pasien Carpal Tunnel Syndrome. Data acuan dalam kajian artikel ini didapatkan dengan penelusuran menggunakan PubMed, Science Direct, dan Google Scholar yang dipublikasikan pada tahun 2011 hingga tahun 2021. Setelah proses pencarian dan seleksi artikel, didapatkan 10 artikel yang disertakan pada literature review ini. Dari seluruh artikel, terdapat satu artikel yang menunjukkan bahwa Carpal Tunnel Syndrome tidak mempengaruhi kualitas hidup. Sedangkan sembilan artikel lainnya menunjukkan bahwa Carpal Tunnel Syndrome dapat mempengaruhi kualitas hidup. Nyeri dan disfungsi tangan mengakibatkan aktivitas terbatas segingga hal ini berkaitan dengan fungsi tubuh, psikologis dan sosial. Gejala-gejala yang dirasakan pada pasien CTS menyebabkan meningkatnya kecemasan, depresi, terbatasnya mengerjakan kegiatan sehari-hari, penurunan efektivitas dalam bekerja, dan penurunan kualitas tidur sehingga menyebabkan pasien mengalami gangguan dalam kualitas hidup mereka. Kata-kata kunci: Carpal Tunnel Syndrome, kualitas hidup, kesehatan fisik dan mental